Relationship between Symptoms of Depression and Anxiety with Major Adverse Cardiac Event in 7 days in Patients with Acute Coronary Syndrome in Cipto Mangunkusumo Hospital - Diah Pravita Sari; E Mudjaddid; Eka Ginanjar; Muhadi (Jurnal Penyakit Dalam Indonesia)
Introduction. Major adverse cardiac events (MACE) are important causes of mortality in acute coronary syndrome (ACS) patients. There are several predictors of the occurence of MACE in patients with ACS, including depression and anxiety. This study aimed to determine the association between depression and anxiety with major adverse cardiac events within 7 days in patients with acute coronary syndrome.